Analysis of the Self-Efficacy Level on Class X Students of SMA Negeri Colomadu in Mathematics Learning - Preti Sakti Wahyu Oktavia; Afif Afghohani M.Kom; Erika Laras Astutiningtyas (Universitas Veteran Bangun Nusantara, 2023)
Student self-efficacy has been impacted by the change from online to face-to-face learning brought on by the COVID-19 epidemic. The goal of this study was to assess the class X students' degree of self-efficacy in learning mathematics for the academic year 2021–2022, at Colomadu Public High School in Karanganyar Regency. Research of this kind is qualitative. Questionnaires, interviews, and documentation were the methods used in this study to collect data. The class from which the research topic was drawn was class X MIPA 5. All of the students in class X MIPA 5 were given the questionnaire, and from the responses, a sample of 6 students was selected for in-person interviews using random and purposive sampling.The results showed that 11.11% or 4 students had a high level of self-efficacy. 66.67% or 24 students have a moderate level of self-efficacy and 22.22% or 8 students have a low level of self-efficacy. It can be seen from the mean classical self-efficacy score of 67.36%, the class X MIPA 5 SMA Negeri Colomadu, Karanganyar Regency, is included in the medium category.